Brown Tumour in the Mandible and Skull Osteosclerosis Associated with Primary Hyperparathyroidism – A Case Report - Popovik-Monevska, Danica (Open Access Maced J Med Sci, 2018)
BACKGROUND: The hyperparathyroidism (HPT) is a condition in which the parathyroid hormone (PTH) levels in the blood are increased. HPT is categorised into primary, secondary and tertiary. A rare entity that occurs in the lower jaw in association with HPT is the so-called brown tumour, which an osteolytic lesion is predominantly occurring in the lower jaw. It is usually a manifestation of the late stage of the disease. Osteosclerotic changes in other bones are almost always associated with renal osteodystrophy in secondary HPT and are extremely rare in primary HPT. This article reports a rare case of a brown tumour in the mandible as the first sign of a severe primary HPT, associated with osteosclerotic changes on the skull. CASE REPORT: A brown tumour in the mandible was diagnosed in 60 - year old female patient with no previous history of systemic disease. The x - rays showed radiolucent osteolytic lesion in the frontal area of the mandible affecting the lamina dura of the frontal teeth, and skull osteosclerosis in the form of salt and pepper sign. The blood analyses revealed increased values of PTH, calcitonin and β – cross-laps, indicating a primary HPT. The scintigraphy of the parathyroid glands showed a presence of adenoma in the left lower lobe. The tumour lesion was surgically removed together with the lower frontal teeth, and this was followed by total parathyroidectomy. The follow - up of one year did not reveal any signs of recurrence. CONCLUSION: It is critical to ensure that every osteolytic lesion in the maxillofacial region is examined thoroughly. Moreover, a proper and detailed systemic investigation should be performed. Patients should undergo regular check-ups to prevent late complications of HPT.